2020
DOI: 10.1111/jace.17459
|View full text |Cite
|
Sign up to set email alerts
|

Relating chemical composition, structure, and rheology in alkali‐activated aluminosilicate gels

Abstract: Model aluminosilicate (N-AS -H) gel systems give insight to the complex reaction occurring in alkali-activated binders, allowing for more precise control over chemical composition and exhibiting simpler kinetics. Small angle neutron scattering, oscillatory rheology, and solid-state NMR were used to characterize N-AS -H gel samples and relate structure, chemical composition, and rheology. Aluminum concentration was varied in the gel samples at fixed silica and sodium concentration. Past the percolation point, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
(185 reference statements)
1
7
0
Order By: Relevance
“…More generally, using Muthukumar's relation for 0 ≤ α ≤ 0.5 yields a range of possible fractal dimensions 2.0 ≤ d f ≤ 2.5 consistent with the RLCA mechanism that is characteristic of these weakly attractive gels. Another recent investigation has also concluded that aluminosilicate gels are formed through RLCA for a range of compositions (20). This analysis suggests that our results should hold for all gels that are in the so-called solid-cluster limit, i.e., gels that display a long-time elastic-like behavior (G ≥ G at low frequencies) with α ≤ 0.5 (5).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…More generally, using Muthukumar's relation for 0 ≤ α ≤ 0.5 yields a range of possible fractal dimensions 2.0 ≤ d f ≤ 2.5 consistent with the RLCA mechanism that is characteristic of these weakly attractive gels. Another recent investigation has also concluded that aluminosilicate gels are formed through RLCA for a range of compositions (20). This analysis suggests that our results should hold for all gels that are in the so-called solid-cluster limit, i.e., gels that display a long-time elastic-like behavior (G ≥ G at low frequencies) with α ≤ 0.5 (5).…”
Section: Discussionsupporting
confidence: 59%
“…S5 and S7), illustrating that, despite slight differences in the chemical balance of the initial reactions, these weak colloidal gels are fractal clusters that are formed through reactionlimited cluster aggregation of smaller building blocks. Recent structural studies on weak colloidal gels with short-range attraction have also reported similarly dense fractal structures with d f 2 (20,27).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The sol sample exhibited good elastic behavior, where tanδ < 1. When tanδ > 1, the increase in tanδ value corresponded to better fluidity [ 30 , 31 , 32 ]. As shown in Figure 6 b, this tanδ value was increased with the rise in temperature for all sol models, indicating that the fluidity of aluminum sol improved with the increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This result strikingly contrasts with previous observations on depletion gels, in which preshear at "low" rates yielded weaker gels with reduced elasticity due to a largely heterogeneous microstructure inherited from the that acquired during shear 17 . Moreover, the viscoelastic spectrum involves a storage modulus that is an increasing function of frequency, whereas the loss modulus is independent or a mildly decreasing function of frequency, similar to aging systems including gels 69,70 and soft glasses 71 . The loss factor tan δ decreases with increasing frequency, which is reminiscent of glass-like behavior, where the slowest relaxation modes dominate 58 .…”
Section: Discussionmentioning
confidence: 99%